Should psychiatric hospitals completely ban smoking?. (4th November 2015) - Arnott, Deborah; Wessely, Simon; Fitzpatrick, Michael
Abstract : A "smoking culture" leads to disproportionate harm among people with serious mental health problems, argue Deborah Arnott and Simon Wessely . But Michael Fitzpatrick thinks it unethical to deprive patients of autonomy and impose treatment